Eleanor - Cooney, Barbara, 1917-2000. (New York : Viking, 1996)
Presents the life of Eleanor Roosevelt, who married a president of the United States and became a great humanitarian.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
4.2
K-3
Center for the Collaborative Classroom Curriculum.
Keywords: Roosevelt, Eleanor, -- 1884-1962 -- Childhood and youth -- Juvenile literature; Roosevelt, Eleanor, -- 1884-1962 -- Childhood and youth; Presidents' spouses -- United States -- Biography -- Juvenile literature; First ladies; Presidents' spouses -- United States -- Biography; Presidents -- United States -- Biography; First ladies